Direct Hot Solid–Liquid Extraction (DH-SLE): A High-Yield Greener Technique for Lipid Recovery from Coffee Beans - Daliane Cláudia de Faria; Maria Eliana Lopes Ribeiro de Queiroz; Fábio Junior Moreira Novaes (Plants)
Soxhlet extraction is a method recommended by the Association of Official Analytical Chemists (AOAC) to determine the lipid content in plant samples. Generally, n-hexane (toxicity grade 5) is used as the solvent (≈300 mL; ≈30 g sample) at boiling temperatures (69 °C) for long times (≤16 h) under a chilled water reflux (≈90 L/h), proportionally aggravated by the number of repetitions and samples determined. In this sense, the technique is neither safe nor sustainable for the analyst or the environment. This article presents the development of an alternative and more sustainable procedure for determining the lipid content in raw Arabica coffee beans. A 33 full factorial design was used to perform direct hot solid–liquid extractions in 4 mL vials, varying the ground grains and solvent ratios, temperatures, and times. An optimal condition resulted in an extractive yield statistically equivalent to Soxhlet, without variation in the composition of the oil fatty acids determined by GC-MS after hole oil transesterification. This procedure was presented as a sustainable alternative to Soxhlet extraction because it does not require water for cooling and needs a smaller volume of solvent (2 mL) and sample mass (0.2 g); it also has a smaller generated residue, as well as requiring a shorter time (1.5 h) and less energy expenditure for extraction.